Poultry meat processing - Alvarado, Christine; Owens, Casey M.; Sams, Alan R. (CRC Press, 2010)
Features chapters on poultry meat nutrition, sanitation, equipment design, biofilm formation, meat quality defects, by-products and animal welfare. This work also covers subjects such as risk assessment in raw and cooked products, instrumental methods for quality evaluation and packaging technology.